2012
DOI: 10.1007/s11604-012-0142-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the renal resistive index and pulsatility index in patients with pleural effusion by duplex Doppler ultrasonography

Abstract: Pleural effusion might result in increased renal impedance as seen in cirrhosis, which is a rather complicated pathophysiological process, without causing any morphological changes in kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In cardiovascular aging, characterized by disorganized medial elastic fibers and increased stiffness of small Frontiers in Physiology frontiersin.org renal arteries, the capacity of such small caliber vessels to dampen pulsatile flow decreases and become more permissive to the transmission of systemic pressure, which in turn could evoke a greater contractile response of the downstream afferent arterioles to increase renal vascular resistance and decrease renal plasma flow and GFR, or otherwise could cause barotraumatic injury to the glomerulus if these mechanisms at the afferent arteriolar level fail (Bidani and Griffin, 2004;Loutzenhiser et al, 2006;Williamson et al, 2008;Bidani et al, 2013). Previous evidence supporting this hypothesis has been obtained from non-invasive assessment of renal hemodynamics by Doppler sonography, which showed increases in the indices of impedance to flow, including resistive index and pulsatility index associated with age-related renal dysfunction (Warshauer et al, 1988;Salgado et al, 1999;Degirmenci et al, 2013). Using the same non-invasive approach in this study, we found that in young mice, elastin haploinsufficiency caused the augmentation of PI and RI as occurs in aging-induced vascular remodeling and a decline in renal function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cardiovascular aging, characterized by disorganized medial elastic fibers and increased stiffness of small Frontiers in Physiology frontiersin.org renal arteries, the capacity of such small caliber vessels to dampen pulsatile flow decreases and become more permissive to the transmission of systemic pressure, which in turn could evoke a greater contractile response of the downstream afferent arterioles to increase renal vascular resistance and decrease renal plasma flow and GFR, or otherwise could cause barotraumatic injury to the glomerulus if these mechanisms at the afferent arteriolar level fail (Bidani and Griffin, 2004;Loutzenhiser et al, 2006;Williamson et al, 2008;Bidani et al, 2013). Previous evidence supporting this hypothesis has been obtained from non-invasive assessment of renal hemodynamics by Doppler sonography, which showed increases in the indices of impedance to flow, including resistive index and pulsatility index associated with age-related renal dysfunction (Warshauer et al, 1988;Salgado et al, 1999;Degirmenci et al, 2013). Using the same non-invasive approach in this study, we found that in young mice, elastin haploinsufficiency caused the augmentation of PI and RI as occurs in aging-induced vascular remodeling and a decline in renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Images of renal arteries were acquired in B-mode with color Doppler setting to identify arterial blood flow. Peak systolic velocity (PSV), least diastolic velocity (LDV), and mean velocity (MV) determined from the renal Doppler waveforms were used to calculate resistive index ( ) and pulsatility index ( ), as previously described ( Warshauer et al, 1988 ; Salgado et al, 1999 ; Degirmenci et al, 2013 ; Jie et al, 2016 ; Koch et al, 2019 ). Each parameter was calculated in triplicate using three separate waveforms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…What's more, in a case report of a patient with acute kidney injury in the course of a large pleural effusion, the authors suggested an interdependence between pleural effusion and kidney injury, which was attributed to neurohormonal derangements, affecting the secretion of natriuretic peptides and/or antidiuretic hormone [ 11 ]. In another study of patients having non-cardiac pleural effusion with normal blood pressure and renal function, the renal artery resistance index (RI) and pulsatility index (PI) of patients having effusion were higher than those normal controls [ 23 ]. The above hypotheses, suggesting that pleural effusion may lead to complicated pathophysiological changes in kidney through neurohumoral regulation, are proposed by clinical manifestations and rationality needs further verification.…”
Section: Discussionmentioning
confidence: 99%